Moral Outrage and the Ethics of Liberation - Lloyd, Vincent (Journal of the Society of Christian Ethics, 2025)
I revisit Jeremiah Wright’s plenary address to the Society of Christian Ethics in 2009, suggesting that he offers a model for liberationist ethics. On that model, the proper approach to Christian ethics is not one that focuses on certain issues, forms of life, or lived experiences. Rather, Christian ethics at its best attempts to integrate all three of these, which I assert is the aim of liberationist ethics. I explore what this could mean for the study and teaching of Christian ethics today.